Abortion and homosexuality prohibitory regimes versus the right to privacy in Nigeria. Issue 3 (2nd July 2020) - Anozie, Miriam Chinyere
Abstract : Although the right to privacy is enshrined in the 1999 Constitution of the Federal Republic of Nigeria as well as several regional and international instruments to which the country is a Party, proper recognition of the right is conspicuously absent in many abortion and homosexual prohibitory legal frameworks enacted by both the federal and state governments. These frameworks may be assailed on the ground that they violate the right to autonomy of affected women and homosexuals in the sense of denial of individually – driven decision-making regarding abortion or sexual preferences. Drawing on the practices in other jurisdictions where the right to privacy is accorded better protection, this paper argues that there is an urgent need for liberalisation of the current anti-abortion and anti-homosexual regimes in the country.